If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-4 + 2b) + -8(6b + -7) = 80 (-4 * 4 + 2b * 4) + -8(6b + -7) = 80 (-16 + 8b) + -8(6b + -7) = 80 Reorder the terms: -16 + 8b + -8(-7 + 6b) = 80 -16 + 8b + (-7 * -8 + 6b * -8) = 80 -16 + 8b + (56 + -48b) = 80 Reorder the terms: -16 + 56 + 8b + -48b = 80 Combine like terms: -16 + 56 = 40 40 + 8b + -48b = 80 Combine like terms: 8b + -48b = -40b 40 + -40b = 80 Solving 40 + -40b = 80 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + -40b = 80 + -40 Combine like terms: 40 + -40 = 0 0 + -40b = 80 + -40 -40b = 80 + -40 Combine like terms: 80 + -40 = 40 -40b = 40 Divide each side by '-40'. b = -1 Simplifying b = -1
| -1/2*0-2 | | -6(1+n)+4(3n+4)=58 | | (x)=7x^2+2x | | -2(3x+6)=20-4x | | 11p-p-8p-p=19 | | -5(4b-6)-2(5b-2)=4 | | 9h+3=5h | | 30x/(x^3) | | 15z-14z=20 | | -4+20-6-(-18)+(-11)= | | -84+10x=3x+63 | | 3/4--16 | | -5x-15=50 | | -2c+30=24 | | -4+20-6(-18)+(-11)= | | 14z-13z=5 | | -10m+2=-8m-8 | | 13d-12d=1 | | -6x+y = -3 | | x/7-1=-6 | | 230/30=345/x | | M/5=175.3 | | -5/6x-1/9x=-102 | | 6y+5y+4= | | 2/3(-2)-4 | | y=-5=1/3x | | 5s-3s=14 | | 12 = g3+ 9 | | 5/13.75=p/24.75 | | 5.04/-9 | | 21.6-1a=5d | | f(x)=7x^2+2x |